Diatom-bound and bulk sediment nitrogen isotope ratios, bulk sediment parameters, Ba/Ti ratio & heterocyst glycolipids in lacustrine sediment cores Figino19-2 and Figino18-2 from lake Lugano, Switzerland - Anja S Studer; Lars Wörmer; Hendrik Vogel; Nathalie Dubois; Maciej Bartosiewicz; Kai-Uwe Hinrichs; Fabio Lepori; Moritz F Lehmann (PANGAEA, 2024)
In two corresponding sediment cores (Figino19-2 and Figino18-2) from the South Basin of Lake Lugano (Switzerland), we have measured diatom-bound nitrogen isotopes, bulk sediment nitrogen and carbon isotopes, organic carbon mass accumulation rates, Ba/Ti ratios and heterocyst glycolipids concentrations to reconstruct the nitrogen cycle and paleoenvironmental conditions of the lake over the past 125 years. Diatom-bound nitrogen isotope analyses were measured using the persulfate denitrifier technique at the University of Basel. Bulk sediment C and N isotope ratios were measured using a Flash EA coupled to a Delta V Plus isotope ratio mass spectrometer at the University of Basel. Ba/Ti ratios were measured by X-ray fluorescence scanning using an ITRAX element core scanner at the University of Bern. Radionuclide activities to constrain the age model were determined by gamma spectrometry in a High-purity Germanium (HPGe) Well Detector at Eawag Dübendorf. Heterocsyst glycolipids were analyzed on a maXis quadrupole time-of-flight mass spectrometer equipped with an electrospray ionization source, and coupled to a Thermo Ultimate 3000RS UHPLC system at the University of Bremen.